Theory of planned behaviour and determinants for cash waqf intention / Ruslaina Yusoff, Shariful Amran Abd Rahman and Wan Nazihah Wan Mohamed - Yusoff, Ruslaina; Abd Rahman, Shariful Amran; Wan Mohamed, Wan Nazihah (2018)
The concept of waqf or donation was introduced during the era of Prophet Mohammad (pbuh) which has fulfilled the important role of satisfying the needs of Islamic community. By some means, waqf is a voluntary act while zakat or giving alms is compulsory to Muslims when their wealth attains the minimum amount of nisab. Waqf refers to retaining and preserving a specific property or asset donated by its owner for the cause of Allah to be used for philanthropy and the benefit of ummah (Farra Munna, Bayu Taufiq, Muhammad Hakimi & Abd. Halim, 2014). Previously, Muslims have the belief that waqf should only be in the form of property like land and building. However, there are other types of waqf which include cash waqf, agricultural machinery, cattle, shares, gold and stocks (Soliha & Muhammad Hakimi, 2015).